POTENSI PEMANFAATAN SAMPAH DALAM MEWUJUDKAN PENGELOLAAN SAMPAH TERPADU DI UNIVERSITAS NAHDLATUL ULAMA NUSA TENGGARA BARAT - Astrini Widiyanti; Taufikul Hadi (Envirotek : Jurnal Ilmiah Teknik Lingkungan, 2022)
UNU NTB campus activities produces inorganic and organic waste. The potential waste amount increasing provides an opportunity for managers to recyle waste into products of economic and environmental value. The purpose of this study to analyze the generation and composition of waste at UNU NTB which is the basic information for conducting integrated waste management. Field observations were made to analyze the amount of waste generated, the weight of the waste, and the percentage of waste composition. The waste generation at UNU NTB reaches 47 liters/day and the weight of waste reaches 3.74 kg/day. The composition of waste at UNU NTB consists of 77% inorganic waste and 23% organic waste. UNU NTB has 773.1 kg/year of plastic waste which generates an economic potential of IDR 2,551,190. Paper waste as much as 326.8 kg/year generates economic potential of Rp. 196,086. Organic waste is analyzed for recycling potential by recyleing organic waste into compost. The economic potential of waste is analyzed based on the price of waste at the UNU NTB Waste Bank. Organic waste at UNU NTB reaches 330.5 kg/year which has an economic potential of Rp. 1,982,880/year with reference to the market price of compost fertilizer of Rp. 6,000/kg. The potential for recycling organic waste into compost is 44 kg/year.